Timelink: um novo “tempo” para a TV digital aberta - Teixeira, Stanley Cunha (2018)
The process of information digitization and the subsequent convergence of digital media are promoting a breakdown of paradigms that will certainly affect the way in which the programming of the open TV channels will be elaborated. Even though it is still unclear what kind of impact this will have on the viewer, there is a trend towards "appification", that is, the transformation of the channels into applications (apps), which will divide space in the screen ecosystem with other software currently used in tablets and smartphones. Thus, the audience dispute will occur not only between broadcasters, but also with other apps that attract attention in mobile media, such as games, social networks, messengers, and so on. As a typical storyteller, TV cannot ignore the interactive language popularized by digital media. However, especially in the case of commercial TVs, one of the main challenges to incorporate the interactivity feature will be to flexibilize the time of the hourly grid to include the "reading time" and the "time of action" that are subjective and different for each viewer. For this, this study proposes the break with the idea of “timeline” to adopt the “Timelink” concept. By replacing the "time line" with the "time network", we suggest another paradigm for the viewer who, from a new technological support, a new architecture and a new information design on the screen, will have the TV time itself to the reach of the remote control. This will allow not only a new experience in front of television, but also the main objective of the Brazilian Digital Terrestrial TV signal, which is to minimize the effects of "digital exclusion", considered by the UN as one of the main factors of social exclusion in Worldwide